2016
DOI: 10.1111/jocd.12208
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical marking and ultrasound‐guided injection of Botulinum type A toxin into the masseter muscles for treating bruxism and its cosmetic effects

Abstract: Ultrasound can be a potent tool for guiding the injection of Botulinum toxin into the masseter muscles. It may contribute to a more personalized procedure, better cosmetic results, and help to avoid potential complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 11 publications
0
29
0
1
Order By: Relevance
“…Ultrasonography has been used as a noninvasive diagnostic technique for diagnosing various diseases in the human body and in particular to analyze the effectiveness of BoNT treatment (e.g., changes in muscle thickness, bite force, and contours of the lower face) in the masseter muscle (Park et al, ; Kim et al, ; Shim et al, ; Quezada‐Gaon et al, ). The present study used ultrasonography to confirm the presence of the DIT in the superficial part of the masseter muscle in healthy young subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonography has been used as a noninvasive diagnostic technique for diagnosing various diseases in the human body and in particular to analyze the effectiveness of BoNT treatment (e.g., changes in muscle thickness, bite force, and contours of the lower face) in the masseter muscle (Park et al, ; Kim et al, ; Shim et al, ; Quezada‐Gaon et al, ). The present study used ultrasonography to confirm the presence of the DIT in the superficial part of the masseter muscle in healthy young subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Lee and his colleagues recently confirmed that ultrasonography‐guided BoNT injection produced good outcomes in correcting asymmetrical smiles (Lee et al, ). Despite its difficulty, the masseter muscle was easier to approach than the facial expression muscles via ultrasonography, which has increased highly in clinical usage (Kiliaridis and Kalebo, ; Bakke et al, ; Raadsheer et al, ; Quezada‐Gaon et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous ultrasound guidance of aesthetic or plastic surgery procedures can improve the precision of injections, drainage procedures and corrections and decrease potential adverse reactions or complications due to injury to neighboring structures [73,74].…”
Section: -Percutaneous Ultrasound Guidance Of Non-surgical and Surgimentioning
confidence: 99%
“…Some of the adverse effects are related to the inadequate placement of injections, or administration of inadequate doses (17,19). Palpation of the hyperactivity areas within the muscle ensures placing the injections in the adequate topographic region, while the depth of the injection can be approximated by initially touching the bone and then slightly retracting the needle.…”
Section: Discussionmentioning
confidence: 99%